2023
DOI: 10.1007/s11356-023-28191-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel model for runoff prediction based on the ICEEMDAN-NGO-LSTM coupling

Abstract: The prediction of runoff trends has always been an essential topic in the eld of hydrological forecasting, accurate and reliable prediction models are of great signi cance to the rational use of water resources. Considering the relatively-low accuracy and poor solving ability of present models for runoff prediction, a new coupled model based on the Improved Complete Ensemble Empirical Mode Decomposition with Adaptive Noise (ICEEMDAN) and Northern Goshawk Optimization (NGO) with Long Short-Term Memory (LSTM) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, with the rapid development of decomposition methods, new methods such as the wavelet packet decomposition (WPD), complete ensemble empirical mode decomposition with adaptive noise (CEEMDAN) and singular spectrum analysis (SSA) demonstrate some advantages in medium-and long-term term runoff forecasting [56,57]. However, it cannot simply be concluded that new methods will always produce the best simulations under all conditions.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, with the rapid development of decomposition methods, new methods such as the wavelet packet decomposition (WPD), complete ensemble empirical mode decomposition with adaptive noise (CEEMDAN) and singular spectrum analysis (SSA) demonstrate some advantages in medium-and long-term term runoff forecasting [56,57]. However, it cannot simply be concluded that new methods will always produce the best simulations under all conditions.…”
Section: Discussionmentioning
confidence: 99%